Genetic variability in curtobacterium flaccumfaciens isolates - de Souza, Valmir Luiz [UNESP]; Maringoni, Antonio Carlos [UNESP]; Krause-Sakate, Renate [UNESP] (My University, 2006)
The bean crop is exposed to many diseases that lead to significant losses, such as the bacterial wilt of common bean caused by Curtobacterium flaccumfaciens pv. flaccumfaciens (Cff). Currently, the bacterial wilt of common bean has been a new problem for the bean crops in several Brazilian regions. The genetic resistance has been the most efficient approach for disease control; however, the possible existence of genetic variability in Cff isolates may be a harmful consequence to the plant improvement especially in relation to the resistance stability and durability. For this reason, this study aimed the evaluation of the genetic variability of 26 Curtobacterium flaccumfaciens isolates, 20 isolates are from bean plants (Cff) collected in different Brazilian regions, four isolates are from international collections (Cff) and two isolates are from citrus endophytic community (C. flaccumfaciens). Two pairs of primers (CffFOR2-CffREV4 and CF4-CF5) were evaluated for its specificity in PCR reaction in the characterization of the 26 isolates studied. In the genetic variability evaluation, the repPCR technique with the REP, ERIC and BOX primers was used. From the electrophoresis pattern generated by the amplification of these repetitive sequences in the genomic DNA of the 26 bacterial isolates, a pertinent analysis (UPGMA – SM) and a dendogram were performed. Considering a 75% similarity index, the isolates were distributed into four distinct groups. The Cff isolates from Paraná and Distrito Federal were separated in distinct groups, while citrus plant endophytic isolates did not form a distinct group from the bean plant ones. The isolates from São Paulo were genetically heterogeneous; and some of them were grouped with the USA, Santa Catarina and citrus plant isolates, while others were grouped with the ones from France and Paraná. The specificity evaluation of the two pairs of primers (CffFOR2-CffREV4 and CF4-CF5) used in the identification of Cff isolates in bean plant and citrus endophytic Curtobacterium flaccumfaciens isolates showed that the CffFOR2-CffREV4 combination was highly specific in the identification for the 26 isolates. The CF4-CF5 primers showed less specificity for two Cff isolateds in bean plant (2928) and (2936) and for the citrus endophytic isolates. Therefore, as an auxiliary tool in the Cff identification in bean plant, the primers CffFOR2-CffREV4 are the best indication.
Variabilidade genética em isolados de curtobacterium flaccumfaciens
Keywords: Additional Phaseolus vulgaris; Bacterial wilt; Rep-PCR